Tumour necrosis factor-α intensifies cancer risk through nutrient-inflammation crosstalk in heart-failure patients: a retrospective cohort study with external validation - Liao, Ruichun; Huang, Jing; Weng, Junfei; Lu, Song; Chen, Jin; Zuo, Yingbing; Jiang, Xiaoting; Peng, Xiaoping (Frontiers in Nutrition, 2025)
BackgroundHeart-failure (HF) survivors experience a disproportionate burden of incident malignancy, yet the biological bridge linking the two syndromes remains elusive. Tumour necrosis factor-α (TNF-α) promotes inflammation-driven oncogenesis, while protein–energy malnutrition amplifies catabolic signalling. We postulated that a nutrient–inflammation interaction score (NIIS), combining circulating TNF-α with the geriatric nutritional risk index (GNRI), would capture this synergistic axis and forecast de-novo cancer in HF.MethodsIn a retrospective hospital cohort, 415 clinically-stable adults ≥ 60 years with chronic HF were followed for a median of 5.2 years. Baseline TNF-α (high-sensitivity ELISA) and GNRI were measured after an overnight fast; NIIS was computed as log-TNF-α × inverse-normalised GNRI. The primary endpoint was re-admission to our hospital for treatment or a scheduled follow-up appointment during which a tumour was detected; events were identified from our hospital admission and outpatient records and adjudicated in blinded fashion. Multivariable Cox models adjusted for demographic, clinical and biochemical covariates quantified associations per 1-SD increment and across tertiles. External validity was tested in 1,912 community-dwelling HF participants.ResultsSixty-two endpoint events (re-admission or follow-up visit at our hospital during which a tumour was detected) occurred (14.9%; 2,122 person-years). Cancer incidence rose step-wise across NIIS tertiles (7.2, 13.7, 23.9%; log-rank p < 0.001). Each 1-SD higher NIIS conferred a 68% greater hazard (HR 1.68, 95% CI 1.32–2.14), exceeding the prognostic strength of TNF-α or GNRI alone. Participants in the highest NIIS tertile had a tripled risk versus the lowest (HR 3.02, 1.71–5.32). Adding NIIS to a clinical model improved Harrell’s C-index from 0.71 to 0.77 (Δ 0.06, p = 0.010) with good calibration; discrimination persisted in the validation cohort (C-index 0.75).ConclusionAn elevated NIIS independently predicts our hospital-defined endpoint of tumour detection at re-admission/follow-up in older adults with HF and enhances risk stratification beyond conventional factors. Routine assessment of nutrient–inflammation crosstalk may enable targeted cardio-oncology surveillance and intervention.